Global Cyber Norms Subsidiarity (UN GGE and UN OEWG) within ASEAN’s Body - Cloramidine, Feline; Wibisono, Ali Abdullah (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2024)
In the context of cybersecurity, ASEAN plays an important role as a normative extension that carries out norm subsidiarity of UN global cyber norms generated from UN GGE and UN OEWG processes. The subsidiarity of norms promoted by ASEAN serves to place any kind of global issues and global interest at the regional level, as well as regional issues and regional interest at the global level. This paper focuses on the implications of ASEAN as a regional institution in the context of cyber norm subsidiarity toward UN global cyber norms. This paper utilizes Acharya’s norm subsidiarity to explain how ASEAN performs a norm subsidiarity of UN’s cybersecurity norms. We argue that ASEAN’s norm subsidiarity role is possible due to the fact that the UN’s cybersecurity norms to regulate the responsible state behavior in cyberspace from the UN GGE and UN OEWG process were symmetrical to ASEAN Way’s emphasis on prioritization member states’ sovereignty and non-intervention principles. Furthermore, this article finds that the implication of ASEAN’s norm subsidiarity to the region’s own cybersecurity accomplishment is still unidentifiable. This article also finds that there are many factors affecting the process of norm subsidiarity in ASEAN, such as the heterogeneity within the institution and the lack of political will of the member states.